A catalyst for preparing isophthalonitrile and a preparation process and application thereof
Patent Information
- Application Number
- CN202610801731.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-20
AI Technical Summary
然而,现有工业催化剂体系仍普遍面临两大技术问题:一是活性组分在长期高温运行条件下易于流失,导致催化剂使用寿命受限;二是更为关键的问题,即氨氧化反应过程中普遍且严重伴生的深度氧化副反应
本发明中制备获得的催化剂可实现间二甲苯转化率≥99.6%,间苯二腈摩尔收率≥91.3%,显著高于现有工业催化剂水平;催化反应后,HCN收率可降至1.0%以下,COX收率可降至3.1%以下,减少了剧毒副产物的生成。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fine chemical catalysis technology, specifically relating to a catalyst for the preparation of isophthalonitrile, its preparation process, and its application. Background Technology
[0002] Isophthalonitrile (IPN, chemical formula C8H4N2) is a crucial organic fine chemical and chemical intermediate. Its primary industrial application value lies in its role as a major synthetic precursor for the broad-spectrum, low-toxicity, and low-residue fungicide "chlorothalonil" (tetrachloroisophthalonitrile). Globally, the annual consumption of chlorothalonil has reached hundreds of thousands of tons, directly driving a stable demand for high-quality isophthalonitrile. On the other hand, isophthalonitrile can be converted to m-phenylenediamine (MXDA) through catalytic hydrogenation. MXDA is a core monomer in the production of high-performance epoxy resin curing agents, polyurethane elastomers, and the specialty nylon resin MXD6. According to relevant industry statistics, the current effective production capacity of isophthalonitrile in my country is approximately 120,000 tons / year, and the direct and indirect downstream industry output value it drives exceeds 8 billion RMB / year, demonstrating the important position of this product in the national economy.
[0003] Currently, the mainstream industrial process for producing isophthalonitrile both domestically and internationally is the gas-phase ammonia oxidation of m-xylene. Since Mitsubishi Gas Chemical Co., Ltd. of Japan first achieved large-scale industrial application of this technology in 1969, the development of its core catalyst has undergone three major technological evolutions: from a single V₂O₅ component, to a V₂O₅-MoO₃ binary system, and now to the widely used V-Mo-Cr / Sb multi-component composite oxide system. Domestically, the independently developed m-509 type silica gel-supported V-Mo-Sb-B-Li-O₂... x The catalyst system has been industrialized, and its stable molar yield of isophthalonitrile is usually maintained in the range of 60% to 66%. However, existing industrial catalyst systems still generally face two major technical problems: first, the active components are prone to loss under long-term high-temperature operation, resulting in limited catalyst life; second, and more critically, is the deep oxidation side reaction that is common and serious in the ammonia oxidation process.
[0004] To address the aforementioned issues, Chinese patent application CN109876794A discloses a dedicated catalyst and its preparation process for the ammonia oxidation reaction to prepare isophthalonitrile. The key technical points are as follows: The catalyst uses silica gel as a support, the main catalyst is composed of three components: V, Mo, and Sb, and the co-catalyst is at least one of components D and E (D is selected from boron, chromium, titanium, phosphorus, nickel, bismuth, manganese, iron, cobalt, copper, zinc, or tin; E is selected from potassium, lithium, sodium, cesium, magnesium, or calcium). The active component composition is expressed as V 1.0 Mo. b Sb cD d E e O x Its core improvement lies in utilizing organosilicon (specifically, SiX) containing lone pair groups on silicon. n Y 4-n Modified silica sol or nitrogen-containing cage-type polysilsesquioxane (Y-POSS) undergoes Lewis acid-base reactions with inorganic elements, thereby enhancing the interaction between inorganic oxides and the support, resulting in more uniform dispersion of the active component, extending the catalyst lifespan from one year to over two years, increasing the molar yield of isophthalonitrile (IPN) to approximately 85%, and achieving a conversion rate exceeding 98%. However, this technology primarily addresses the shortened lifespan caused by desorption of the active component due to its physical stability and dispersion uniformity. It still lacks effective methods to suppress the deep oxidation side reactions commonly associated with ammonia oxidation.
[0005] As is well known to those skilled in the art, the ideal stoichiometric formula for the ammoxidation of m-xylene to prepare isophthalonitrile is as follows: C6H4(CH3)2 + 2NH3 + 3O2 → C6H4(CN)2 + 6H2O. Based on this theoretical calculation, the theoretical consumption of liquid ammonia for producing 1 ton of isophthalonitrile is only about 0.27 tons. However, in actual industrial production, due to the excessively strong and difficult-to-control surface-active oxygen species on existing V-Mo-Sb catalysts, at reaction temperatures above 400℃, the target product, isophthalonitrile, is easily further oxidized to carbon oxides (CO). X The reaction produces highly toxic hydrogen cyanide (HCN). This side reaction results in a typical domestic industrial plant consuming 0.9 to 1.2 tons of liquid ammonia per ton of product, which is 3 to 4 times the theoretical stoichiometric consumption. Simultaneously, the molar loss rate of m-xylene due to deep oxidation is as high as 15% to 25%. The direct consequences include: high raw material waste, complex ammonia removal and post-treatment costs, and additional energy consumption from tail gas catalytic combustion. These combined can account for 18% to 22% of the total production cost, becoming one of the main technical bottlenecks restricting the industry's competitiveness. The reason for this is that although existing catalysts have high initial activity, the oxidizing power of their surface active oxygen species is too strong and difficult to control. Under high-temperature (>400℃) reaction conditions, the target product, isophthalonitrile, is easily further oxidized to CO. X And highly toxic HCN and other deep oxidation byproducts. Summary of the Invention
[0006] To address the problems existing in the prior art, this invention aims to provide a catalyst for the preparation of isophthalonitrile that can significantly suppress deep oxidation side reactions while maintaining high conversion and high yield, as well as its preparation process and application. This has significant practical significance and application value for reducing industrial ammonia consumption, reducing by-product generation, and improving the economic efficiency of the equipment.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A process for preparing a catalyst for the preparation of isophthalonitrile includes the following steps: (1) Hydrolyze siloxane with water to obtain hydrolysate; Oxalic acid, vanadium pentoxide, ammonium molybdate hydrate, and potassium antimony tartrate are mixed evenly in solution to obtain mixture A; Citric acid and soluble cerium salt are mixed evenly in water, and then boric acid and lithium carbonate are added and mixed evenly to obtain mixture B; Melamine and water were mixed evenly to obtain mixture C; The hydrolysate, mixture A, mixture B, and mixture C are mixed evenly, then silica sol and water are added and mixed evenly to obtain a spray slurry; then spray dried to obtain the precursor powder. (2) The precursor powder obtained in step (1) is kept at 300-350℃ for 3-5 hours under a protective atmosphere, then cooled to 120-150℃, and then kept at 500-550℃ for 6-8 hours in an air atmosphere and cooled to obtain the product.
[0008] In this scheme, a stable structure is constructed on the catalyst surface through a series of integrated synergistic processes, namely "siloxane pre-anchoring - multi-metal component stepwise complexation - melamine nitrogen source interface modification - dual-atmosphere stepwise calcination", resulting in a supported composite oxide catalyst with high activity and high selectivity. The "dual-atmosphere stepwise calcination" process allows melamine to first undergo low-temperature cracking, and then form a stable surface structure during air activation, further reducing the excessive adsorption and activation of the target product on the catalyst surface.
[0009] Preferably, the siloxane in step (1) is aminoethylaminopropyl polydimethylsiloxane.
[0010] In this scheme, the preferred siloxane is aminoethylaminopropyl polydimethylsiloxane. While hydrolyzing and polycondensing to form a silica gel network, the terminal amino functional groups coordinate or electrostatically adsorb with active metal ions such as V, Mo, and Sb in the solution, achieving molecular-level pre-anchoring of the active components. This effectively prevents metal agglomeration during subsequent spray drying and calcination processes, ensuring a high degree of dispersion of the active centers.
[0011] Preferably, the hydrolysate in step (1) is prepared by adding siloxane dropwise to water and stirring for 30-40 minutes.
[0012] Preferably, in step (1), the amount of siloxane used is 10-12g of siloxane per 50-100mL of water.
[0013] Preferably, in step (1), the oxalic acid, vanadium pentoxide, ammonium molybdate hydrate, and potassium antimony tartrate are mixed evenly in the solution by first mixing vanadium pentoxide with the oxalic acid solution evenly, then adding ammonium molybdate hydrate and mixing evenly, and then adding potassium antimony tartrate and mixing evenly.
[0014] In this scheme, vanadium pentoxide is preferably mixed with oxalic acid solution, followed by the sequential addition of ammonium molybdate hydrate and potassium antimony tartrate. Oxalic acid can form a stable and soluble vanadium oxalate complex with vanadium pentoxide, avoiding incomplete dissolution of V₂O₅ or local overheating. Stepwise addition allows the active components V, Mo, and Sb to form uniform complexes sequentially, achieving atomic-level dispersion. On the one hand, this effectively prevents excessively high local concentrations, particle precipitation, and splashing, improving the uniformity and batch stability of the mixture; on the other hand, it makes the distribution of active components more uniform and the crystal phase composition more controllable, thereby improving the catalytic activity of the catalyst.
[0015] Preferably, the temperature of the oxalic acid solution is 75-85℃.
[0016] Preferably, vanadium pentoxide is added in batches, with each batch containing 2-3g of vanadium and the time interval between the two additions being 2-5 minutes.
[0017] Preferably, the mass ratio of oxalic acid to vanadium pentoxide in step (1) is 35-40:10-12.
[0018] Preferably, in step (1), the mass ratio of vanadium pentoxide to ammonium molybdate hydrate is 10-12:20-25.
[0019] Preferably, in step (1), the ammonium molybdate hydrate is added and mixed evenly while stirring at 75-85°C for 20-30 minutes.
[0020] Preferably, in step (1), the citric acid and soluble cerium salt are mixed evenly in water by adding citric acid to water and mixing evenly, and then adding soluble cerium salt and mixing evenly. The temperature when adding citric acid to water and mixing evenly is 50-60℃.
[0021] In this scheme, it is preferable to first rapidly dissolve the cerium salt at 50-60℃ to form a citric acid solution, thereby constructing a uniform complexation environment, and then add the soluble cerium salt. The cerium ions are fully complexed and stabilized, achieving molecular-level dispersion, which avoids hydrolysis and precipitation after the cerium salt is added directly, thereby improving the catalyst selectivity and catalytic stability.
[0022] Preferably, the soluble cerium salt in step (1) is any one of cerium nitrate, cerium chloride, and cerium acetate. Cerium nitrate is preferred.
[0023] Preferably, the mass ratio of soluble cerium salt to citric acid in step (1) is 8-9:5-10.
[0024] In this scheme, citric acid can fully complex and coat cerium ions at this ratio, ensuring that cerium salts are completely dissolved and that there is no excessive carbon residue affecting crystallization.
[0025] Preferably, the mass ratio of soluble cerium salt to lithium carbonate in step (1) is 8-9:0.2-3.
[0026] The synergistic effect of appropriate amounts of lithium and cerium can alter the surface electronic properties of the catalyst, enhance the selectivity of lattice oxygen, and reduce the peroxidation tendency of the target product.
[0027] Preferably, the mass ratio of soluble cerium salt to boric acid in step (1) is 8-9:2-3.
[0028] Preferably, the mass ratio of soluble cerium salt to melamine in step (1) is 8-9:10-25.
[0029] In this scheme, controlling the mass ratio of soluble cerium salt to melamine to be 8-9:10-25 allows for optimal synergistic matching between the melamine pyrolysis structure and cerium oxide, ensuring sufficient nitrogen sites to modify the active interface, weakening strong oxidizing oxygen species, and allowing Ce to... 4+ / Ce 3+ To effectively leverage the regulatory role of lattice oxygen, and to avoid the overabundance of one component leading to the suppression or weakening of the other's function.
[0030] Preferably, the temperature at which melamine and water are mixed evenly in step (1) is 80-95°C.
[0031] Preferably, in step (1), the melamine is mixed with water in batches at a speed of 600-800 rpm to achieve uniform mixing.
[0032] Preferably, the time interval between each addition is 3-5 minutes.
[0033] Preferably, after adding melamine, stir at 80-95℃ for 20-30 minutes.
[0034] In this scheme, melamine is added to water in batches at a speed of 600-800 rpm, which can avoid local encapsulation and agglomeration, fully disperse and remove air bubbles, make the suspension uniform and stable, and prevent sedimentation and agglomeration, thus ensuring the uniformity of the catalyst's microstructure.
[0035] Preferably, the temperature at which the hydrolysate, mixture A, mixture B, and mixture C are mixed evenly in step (1) is 50-60℃. The stirring speed during mixing is 360-420 rpm.
[0036] Preferably, in step (1), the hydrolysate, mixture A, mixture B, and mixture C are mixed evenly by sequentially adding mixture B, hydrolysate, and mixture C to mixture A. After addition, the mixture is stirred at 60-70℃ for 30-40 minutes. The stirring speed is 600-720 rpm.
[0037] In this scheme, a specific feeding sequence can regulate the precipitation rate between different components, prevent colloidal aggregation, form a precursor with a multi-layered porous structure, improve the mass transfer efficiency of the catalyst, and facilitate product desorption, which is beneficial to improving the selectivity of the catalyst.
[0038] Preferably, in step (1), the amount of silica sol added is 150-200 mL of silica sol for every 150 mL of mixture A.
[0039] Preferably, the SiO2 content in the silica sol is 25%-35%.
[0040] Preferably, in step (1), after adding silica sol, the amount of water added is 200-300 mL for every 150 mL of mixture A. The temperature of the added water is 50-60℃. The solid content of the spray slurry is 30%-35%.
[0041] In this scheme, the solid content of the spray slurry is preferably controlled at 30%-35%. This range of solid content ensures the spheroidization integrity of the droplets during spray drying, resulting in catalyst microspheres with optimal sphericity and compressive strength.
[0042] Preferably, the protective atmosphere in step (2) is either nitrogen or argon.
[0043] Preferably, the heating rate in step (2) to 300-350℃ is 2-3℃ / min.
[0044] Preferably, in step (2), before holding at 500-550℃ in air, the temperature is first held at 230-270℃ for 1-2 hours, then at 420-460℃ for 2-3 hours, and then at 500-550℃. The heating rate during the holding at 230-270℃ is 1-2℃ / min. The heating rate during the holding at 420-460℃ is 2-3℃ / min.
[0045] In this scheme, a stepped heating calcination method is adopted, which can effectively avoid the crystal form mutation of the active phase due to excessively rapid heating. The salt decomposition, partial removal of nitrogen species and formation of composite oxide lattice are achieved step by step to build a stable structure.
[0046] The present invention also provides a catalyst for the preparation of isophthalonitrile obtained by the above method.
[0047] Compared with the prior art, the beneficial effects of the present invention are: The catalyst prepared in this invention can achieve a m-xylene conversion rate of ≥99.6% and a isophthalonitrile molar yield of ≥91.3%, significantly higher than the levels of existing industrial catalysts; after the catalytic reaction, the HCN yield can be reduced to below 1.0%, and the CO yield can be reduced to below 1.0%. X The yield can be reduced to below 3.1%, thus reducing the generation of highly toxic byproducts.
[0048] In this invention, diaminosiloxane is preferably used to achieve molecular-level pre-anchoring of the active component, which improves the dispersion uniformity and stability of the active component and makes it less prone to loss of the active component, so as to facilitate the construction of a stable supported composite oxide structure and maintain high catalytic activity. Detailed Implementation
[0049] The technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0050] Unless otherwise specified, all raw materials used in the examples and comparative examples are commercially available.
[0051] Example 1 The preparation process of the catalyst for preparing isophthalonitrile in this embodiment includes the following steps: (1) Add 50 mL of deionized water to a 250 mL three-necked flask and adjust the initial temperature to 30 ± 1 °C. Then, under magnetic stirring at 300 rpm, add 12.0 g of aminoethylaminopropylpolydimethylsiloxane (AEAPS) dropwise over 10 min. After the addition is complete, continue stirring for 30 min to obtain hydrolyzed AEAPS solution. The solution is approximately milky white and semi-transparent. Take another 500mL three-necked flask, add 150mL of deionized water and heat to 80±2℃. While mechanically stirring at 500rpm, add 38.5g of H₂C₂O₄·2H₂O to dissolve it, obtaining an oxalic acid solution. Then, slowly add 10.90g of V₂O₅ powder in batches (approximately 2g each time) within 15 minutes, and continue stirring for 40 minutes until the solution gradually changes from orange-red to blue. Finally, add 24.70g of ammonium molybdate hydrate (NH₄)₆Mo₇O₇ all at once. 24 Add 4H2O, maintain 80℃ and continue stirring for 20 minutes; then add 35.40g of potassium antimony tartrate and stir for 30 minutes to obtain a deep blue-green solution (denoted as solution A). (2) Take another 100mL beaker, add 40mL of distilled water and heat to 60±2℃, add 6.0g of hydrated citric acid, stir until completely dissolved, then add 8.63gCe(NO3)3·6H2O, stir for 15min, then add 0.75gLi2CO3 and 2.46gH3BO3, stir magnetically at 400rpm (open) for 20min until completely dissolved, and record as solution B; Then, take another 100mL beaker, add 50mL of distilled water and heat to 90±2℃. Add 15.0g of melamine in 5 portions (3.0g each time, 3min apart) while stirring vigorously at 600rpm. After the addition is complete, keep warm and stir for 30min to obtain a uniform milky white suspension (referred to as solution C). (3) Cool the A liquid obtained in step (1) to 50±2℃, and then slowly add the B liquid obtained in step (2) (about 3 min to be added), the hydrolyzed AEAPS liquid obtained in step (1) (about 5 min to be added), and the C liquid obtained in step (2) (about 10 min to be added, added while hot) under mechanical stirring at 400 rpm. After all the liquids are added, heat the temperature to 60±2℃ and stir at 600 rpm for 40 min to form a uniform slurry. Then, under vigorous stirring, slowly add 180 mL of silica sol over 20 min (feeding rate 9 mL / min, SiO2 content 30%, particle size 10-15 nm, pH=3.0), continue stirring for 30 min, add 250 mL of distilled water at 50℃ in 3 portions, and continue stirring for 15 min to obtain the final spray slurry (slurry pH=4.5, solid content approximately 32 wt%). The prepared slurry was fed into a spray dryer for spray drying to obtain a grayish-white precursor powder with an average particle size of about 70 μm. (4) Spread the precursor powder obtained in step (3) in a ceramic boat (loading thickness <10mm), place it in a tube furnace, and raise it from room temperature to 300℃ at a heating rate of 2℃ / min under the protection of a high-purity N2 atmosphere (flow rate 200mL / min, purity ≥99.999%), then keep it at that temperature for 3h, and then cool it naturally to 150℃. The powder was then transferred to a muffle furnace and heated in air according to the following procedure: first, it was heated to 250℃ at 1℃ / min and held for 1 hour; then it was heated to 450℃ at 2℃ / min and held for 2 hours; finally, it was heated to 550℃ at 1.5℃ / min and held for 6 hours. After naturally cooling to room temperature, it was ground and sieved to collect 30-120μm microspheres, which were then obtained.
[0052] Example 2 The preparation process of the catalyst for the preparation of isophthalonitrile in this embodiment differs from that in Example 1 only in that: In step (2), the amount of melamine added is 25.0g, and the rest are the same as in Example 1.
[0053] Example 3 The preparation process of the catalyst for the preparation of isophthalonitrile in this embodiment differs from that in Example 1 only in that: In step (2), the amount of melamine added is 20.0g, and in step (4), the heat preservation time at 300℃ is 5h. All other steps are the same as in Example 1.
[0054] Example 4 The preparation process of the catalyst for the preparation of isophthalonitrile in this embodiment differs from that in Example 1 only in that: In step (2), the amount of Ce(NO3)3·6H2O used is 17.26g, and the others are the same as in Example 1.
[0055] Example 5 The preparation process of the catalyst for the preparation of isophthalonitrile in this embodiment differs from that in Example 1 only in that: The temperature of 300°C in step (4) is replaced with 350°C, and the rest is the same as in Example 1.
[0056] Example 6 The preparation process of the catalyst for the preparation of isophthalonitrile in this embodiment differs from that in Example 1 only in that: In step (4), the powder is transferred to a muffle furnace and heated in an air atmosphere according to the following procedure: first, it is heated to 250℃ at 1℃ / min and held for 1h, then heated to 400℃ at 2℃ / min and held for 2h, and finally heated to 500℃ at 1.5℃ / min and held for 6h; after naturally cooling to room temperature, it is ground and sieved.
[0057] Everything else is the same as in Example 1.
[0058] Comparative Example 1 The difference between this comparative example and Example 1 is that step (2) is: (2) Take another 100mL beaker, add 40mL of distilled water and heat to 60±2℃, add 6.0g of hydrated citric acid, stir until completely dissolved, then add 8.63gCe(NO3)3·6H2O, stir for 15min, then add 2.59gLi2CO3 and 2.46gH3BO3, stir magnetically at 400rpm (open) for 20min until completely dissolved, and record as solution B; Then take another 100mL beaker, add 50mL of distilled water and heat to 90±2℃ to obtain solution C.
[0059] Everything else is the same as in Example 1.
[0060] Comparative Example 2 The difference between this comparative example and Example 1 is that step (2) is: (2) Take another 100mL beaker, add 40mL of distilled water and heat to 60±2℃, add 6.0g of hydrated citric acid, stir until completely dissolved, then add 0.245gLi2CO3 and 2.46gH3BO3, and stir magnetically at 400rpm (open) for 20min until completely dissolved, and record it as solution B; Then, take another 100mL beaker, add 50mL of distilled water and heat to 90±2℃. Add 15.0g of melamine in 5 portions (3.0g each time, 3min apart) while stirring vigorously at 600rpm. After the addition is complete, keep warm and stir for 30min to obtain a uniform milky white suspension (referred to as solution C).
[0061] Everything else is the same as in Example 1.
[0062] Experimental Example The catalysts prepared in Examples 1-6 and Comparative Examples 1-2 were used to evaluate their catalytic performance. The specific testing method was as follows: 20g of catalyst (bed height approximately 60mm) was loaded into a quartz tube fixed-bed reactor with an inner diameter of 30mm and a length of 800mm. 20g of quartz sand was filled at the top and bottom as a preheating layer and a distribution layer, respectively. The molar ratio of the reactants was m-xylene:NH3:air = 1:5:35; the preheating temperature was 200℃; the reaction temperature was 693±1K (420℃); and the catalyst loading WHSV = 100g(m-xylene) / (kg·h). The reaction products were subjected to two-stage condensation and absorption using a cold trap (-5℃) and acetone absorbent (0℃). The tail gas was analyzed online by GC-TCD for CO. X The N2 content was analyzed in the condensate by GC-FID (HP-5MS capillary column, 50m×0.32mm×0.25μm) to determine the content of components such as isophthalonitrile (IPN) and mononitrile. The conversion rate of m-xylene, the yield of IPN, the yield of mononitrile, the yield of HCN, and the CO content were calculated. X Yield. The test results are shown in Table 1.
[0063] Table 1 Performance Test Results
[0064] As shown in Table 1, the catalysts prepared in each embodiment of this invention exhibit excellent ammonia oxidation catalytic performance. Among them, Example 1 shows the best performance in all aspects, with a m-xylene conversion rate of 99.6%, an isophthalonitrile (IPN) molar yield as high as 91.3%, a mononitrile yield of only 3.2%, an HCN yield of 1.0%, and a CO yield of 1.0%. X The yield was 3.1%, achieving a balance between high activity and high selectivity, which is significantly better than the existing technology.
[0065] Compared to Example 1, in Example 2, after increasing the amount of melamine, the catalyst dispersibility deteriorated, surface powder appeared, and the conversion rate and yield decreased significantly, indicating that there is an optimal addition range for melamine.
[0066] In Example 3, while increasing the amount of melamine, the pre-pyrolysis time was extended, and the yield rebounded, basically approaching the optimal level of Example 1, indicating that the amount of melamine added and the pre-pyrolysis conditions have a synergistic optimization effect.
[0067] In Example 4, the amount of cerium salt was increased, CO x The yield dropped to a minimum of 2.7%, but the conversion rate decreased slightly, indicating that the synergistic regulatory effect of Li and Ce depends on the appropriate Ce / Li ratio.
[0068] In Example 5, the N2 pre-decomposition temperature was increased to 350°C, and the IPN yield decreased to 89.6%, indicating that 300°C is the optimal temperature window for forming a stable interface structure.
[0069] In Example 6, the air activation temperature was lowered to 500°C. The active phase crystallization was insufficient, and the conversion rate and yield both decreased significantly, indicating that 550°C is a necessary condition to ensure the complete formation of the active phase of the composite oxide.
[0070] In Comparative Example 1, without the addition of melamine, an interfacial layer structure could not be formed on the catalyst surface; the IPN yield decreased to 84.2%, and the HCN and CO yields were also reduced. x The significantly increased yield indicates that the nitrogen anchoring point constructed with melamine is the core of inhibiting deep oxidation and improving the selectivity of the target product.
[0071] Comparative Example 2, without the addition of cerium salt, showed a decrease in IPN yield and CO. x The increase in HCN yield indicates that cerium Lithium synergistically regulates lattice oxygen and surface acidity / alkalinity, effectively reducing the occurrence of oxidation side reactions.
[0072] In summary, this invention utilizes aminoethylaminopropyl polydimethylsiloxane pre-anchoring, V... Mo Sb atomic-level complexation, Ce Li The integrated design of B-type additive synergy, melamine nitrogen modification, and dual-atmosphere step calcination can build a stable structure on the catalyst surface. While ensuring high conversion rate, it can significantly suppress the deep oxidation side reaction of isophthalonitrile, greatly reduce raw material consumption and by-product generation, and its overall performance is superior to the industry level.
[0073] The above are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A process for preparing a catalyst for the preparation of isophthalonitrile, characterized in that, Includes the following steps: (1) Hydrolyze siloxane with water to obtain hydrolysate; Oxalic acid, vanadium pentoxide, ammonium molybdate hydrate, and potassium antimony tartrate are mixed evenly in solution to obtain mixture A; Citric acid and soluble cerium salt are mixed evenly in water, and then boric acid and lithium carbonate are added and mixed evenly to obtain mixture B; Melamine and water were mixed evenly to obtain mixture C; The hydrolysate, mixture A, mixture B, and mixture C are mixed evenly, then silica sol and water are added and mixed evenly to obtain a spray slurry; then spray dried to obtain the precursor powder. (2) The precursor powder obtained in step (1) is kept at 300-350℃ for 3-5 hours under a protective atmosphere, then cooled to 120-150℃, and then kept at 500-550℃ for 6-8 hours in an air atmosphere and cooled to obtain the product.
2. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, In step (1), the siloxane is aminoethylaminopropyl polydimethylsiloxane.
3. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, In step (1), the oxalic acid, vanadium pentoxide, ammonium molybdate hydrate, and potassium antimony tartrate are mixed evenly in the solution. First, vanadium pentoxide is mixed evenly with the oxalic acid solution, then ammonium molybdate hydrate is added and mixed evenly, and then potassium antimony tartrate is added and mixed evenly.
4. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, In step (1), the mass ratio of soluble cerium salt to citric acid is 8-9:5-10.
5. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, In step (1), the mass ratio of soluble cerium salt to lithium carbonate is 8-9:0.2-3.
6. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, In step (1), the mass ratio of soluble cerium salt to melamine is 8-9:10-25.
7. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, In step (1), the hydrolysate, mixture A, mixture B, and mixture C are mixed evenly by adding mixture B, hydrolysate, and mixture C to mixture A in sequence.
8. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, The solid content of the spray slurry is 30%-35%.
9. The preparation process of the catalyst for preparing isophthalonitrile according to claim 1, characterized in that, In step (2), before heat preservation at 500-550℃ in air atmosphere, heat preservation is first carried out at 230-270℃ for 1-2 hours, then heat preservation is carried out at 420-460℃ for 2-3 hours, and then heat preservation is carried out at 500-550℃.
10. A catalyst for the preparation of isophthalonitrile, characterized in that, It is prepared using the preparation process for the catalyst for preparing isophthalonitrile according to any one of claims 1-9.
Citation Information
Patent Citations
Special catalyst for preparing m-phthalonitrile through ammoxidation reaction as well as preparation method and application thereof
CN109876794A